Multimodal Short Video Strategies of Independent Artists Navigating Algorithmic Gatekeeping on TikTok - Suurhasko, Noora (My University, 2026)
Independent artists today navigate a digital music market defined by oversupply and algorithmic gatekeeping—conditions in which visibility is structurally scarce, not incidentally so. On TikTok, short-form videos must achieve immediate interpretability to circulate within an interest-graph feed, yet the design logic behind high-engagement TikTok posts has received limited scholarly attention. Existing research has examined platform dynamics, branding, and short-form communication in relative isolation. This study examines how independent artists design multimodal content within platform-native short-form video posts to generate engagement, advancing an artist-branding perspective on content design as a sociomaterial practice. The study is guided by three research questions that move from surface to structure to strategy: what content features and communicative messages characterize high-engagement posts; how those features organize narrative meaning through micro-storytelling sequences; and what strategic archetypes of artist-brand communication emerge when both are considered together. The analysis integrates a sociomaterial perspective on platform visibility with a stimulus–staging–response (S–St–R) framework, distinguishing among stimulus (multimodal surface cues), staging (their temporal sequencing), and response (platform-visible audience engagement). In combination, these lenses reframe short-form content design as a relational process at the level of content design—one in which the relations between elements carry analytical weight equal to the elements themselves. To examine these questions, the study adopts a qualitative, abductive approach, drawing on a purposive sample of 30 high-engagement TikTok videos published by 10 anonymized independent artists in early 2025. Each post is treated as a multimodal unit of analysis and analyzed through Visual-Verbal Video Analysis (VVVA)—a method purpose-built for holding audiovisual cues, micro-temporal narrative structures, and engagement traces within a single analytical frame. The findings demonstrate that high-engagement TikTok content appears to rely on recurring multimodal patterns that establish immediate legibility. Meaning is structured through three micro-storytelling patterns—Immediate Loops, Revealed Progressions, and Escalation Arcs—which, combined with message-level orientations toward entertainment value and emotional value, yield four analytically distinct strategic archetypes of artist-brand communication: Immediate Musical/Aesthetic Loops, Proof-to-Reveal Configurations, Process-to-CTA Funnels, and Escalation-to-Punchline Formats. The study introduces configuration fluency as the mechanism by which independent artists align multimodal elements, narrative sequencing, and platform-native affordances, proposing legibility-first content design as a practical principle for algorithmically mediated environments and offers a basis for future research at the intersection of platform studies, multimodal communication, and independent artist practice.

Nykypäivän digitaalisia musiikkimarkkinoita leimaavat sisällön ylitarjonta ja algoritminen portinvartijuus, jotka tekevät näkyvyydestä rakenteellisesti niukan resurssin itsenäisille artisteille. TikTokin käyttäjäkohtaisesti räätälöity sisältösyöte edellyttää markkinointiviestinnältä välitöntä ymmärrettävyyttä: katsojan on hahmotettava videon idea ja arvo sekunneissa, muuten algoritmi ohittaa sen. Korkea sitoutuminen (katselut, tykkäykset ja jaot) on keskeinen onnistumisen mittari, mutta sen taustalla olevaa sisältölogiikkaa on tutkittu vähän. Aiempi tutkimus on tarkastellut alustojen dynamiikkaa, artistibrändäystä ja lyhytvideoviestintää pääosin erillisinä ilmiöinä. Tässä tutkielmassa analysoidaan, miten itsenäiset artistit suunnittelevat multimodaalista lyhytvideosisältöä yleisön sitoutumisen vahvistamiseksi. Tutkimus tarkastelee sisällönsuunnittelua sosiomateriaalisena käytäntönä ja kysyy, millaiset piirteet luonnehtivat korkean sitoutumisen julkaisuja, miten ne muodostavat merkityksiä mikrotarinankerronnassa ja millaisia strategisia arkkityyppejä artistibrändiviestinnässä voidaan tunnistaa. Teoreettinen viitekehys yhdistää alustanäkyvyyden sosiomateriaalisen tarkastelun ja ärsyke–jäsentely–vaste-mallin (S–St–R), jossa erotetaan videon multimodaaliset ominaisuudet, niiden ajallinen järjestyminen ja katsojan vaste. Näin lyhytvideosisällön suunnittelu jäsentyy prosessina, jossa elementtien väliset suhteet ovat keskeisiä. Tutkimus on laadullinen ja abduktiivinen. Aineisto koostuu 30 korkean sitoutumisen TikTok-videosta, jotka on kerätty kymmenen anonymisoidun itsenäisen artistin tileiltä alkuvuodesta 2025 ja analysoitu visuaalis-verbaalisen videoanalyysin (VVVA) avulla. Tulokset osoittavat, että korkean sitoutumisen sisällöt perustuvat toistuviin multimodaalisiin malleihin ja jäsentyvät kolmeen mikrotarinankerronnan jaksoon: toistoon, vaiheittaiseen paljastamiseen ja jännitteen huipentamiseen. Näiden pohjalta voidaan tunnistaa neljä strategista arkkityyppiä: loop‑rakenteinen välitön immersio, paljastukseen etenevä kerronta, prosessista toimintakehotukseen johtava suppilo sekä huipennukseen rakentuva dramaturgia. Tutkielman keskeinen kontribuutio on konfiguraatiosujuvuuden käsite, joka kuvaa, miten multimodaaliset elementit, tarinankerronnan ajallinen rakenne ja alustan tekniset reunaehdot sovitetaan yhteen. Mitä sujuvammin nämä tasot yhdistyvät, sitä tehokkaammin sisältö puhuttelee katsojaa. Tutkielma esittää algoritmiohjattuihin ympäristöihin suunnitteluperiaatteen, joka korostaa sisällön välitöntä ymmärrettävyyttä ja avaa uusia tutkimusmahdollisuuksia alustatutkimuksen, multimodaalisen viestinnän ja itsenäisen artistitoiminnan risteyskohdassa.
Keywords: Independent artists; TikTok; Artist branding; Algorithmic gatekeeping; Multimodal content design; Micro-storytelling; Configuration fluency; Visual–Verbal Video Analysis (VVVA); itsenäiset artistit; artistibrändäys; algoritminen portinvartijuus; multimodaalinen sisällönsuunnittelu; mikrotarinankerronta; konfiguraatiosujuvuus; visuaalis-verbaalinen videoanalyysi